Individual MHCI-Restricted T-Cell Receptors are Characterized by a Unique Peptide Recognition Signature - Wooldridge, Linda (Frontiers in Immunology, 2013)
Effective immunity requires that a limited TCR repertoire is able to recognize a vast number of foreign peptide-MHCI (peptide-major histocompatibility complex class I) molecules. This challenge is overcome by the ability of individual TCRs to recognize large numbers of peptides. Recently, it was demonstrated that MHCI-restricted TCRs can recognize up to 106 peptides of a defined length. Astonishingly, this remarkable level of promiscuity does not extend to peptides of different lengths, a fundamental observation that has broad implications for CD8+ T-cell immunity. In particular, the findings suggest that effective immunity can only be achieved by mobilization of “length-matched” CD8+ T-cell clonotypes. Overall, recent findings suggest that every TCR is specific for a unique set of peptides, which can be described as a unique “peptide recognition signature” (PRS) and consists of three components: (1) peptide length preference, (2) number of peptides recognized; and, (3) sequence identity (e.g., self versus pathogen derived). In future, the ability to de-convolute peptide recognition signatures across the normal and pathogenic repertoire will be essential for understanding the system requirements for effective CD8+ T-cell immunity and elucidating mechanisms which underlie CD8+ T-cell mediated disease.